2005
DOI: 10.1124/jpet.105.091256
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Agonist Binding to Human Dopamine Receptor Subtypes by l-Prolyl-l-leucyl-glycinamide and a Peptidomimetic Analog

Abstract: The present study was undertaken to investigate the role of the hypothalamic tripeptide L-prolyl-L-leucyl-glycinamide (PLG) and its conformationally constrained analog 3(R)-[(2(S)-pyrrolidinylcarbonyl)amino]-2-oxo-1-pyrrolidineacetamide (PAOPA) in modulating agonist binding to human dopamine (DA) receptor subtypes using human neuroblastoma SH-SY5Y cells stably transfected with respective cDNAs. Both PLG and PAOPA enhanced agonist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(93 citation statements)
references
References 31 publications
(33 reference statements)
5
84
4
Order By: Relevance
“…Previous research from our lab has demonstrated that the endogenous brain tripeptide PLG and its analog PAOPA (Figure 1) modify dopaminergic neurotransmission by acting as allosteric modulators of the DA D 2 receptor (Johnson et al 1986;Mishra 1983;Mishra et al 1983;Mishra et al 1997;Verma et al 2005;Chiu et al 1981;Chiu et al 1983;Raghavan et al 2009;Srivastava et al 1988;Verma et al 2005). These compounds have been shown to increase agonist binding to DA D 2 receptors without affecting antagonist binding, and prevent conversion of high-affinity state DA receptors (D 2 High ) to their low-affinity state (D 2 Low ) (Mishra et al 1990;Srivastava et al 1988;Verma et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research from our lab has demonstrated that the endogenous brain tripeptide PLG and its analog PAOPA (Figure 1) modify dopaminergic neurotransmission by acting as allosteric modulators of the DA D 2 receptor (Johnson et al 1986;Mishra 1983;Mishra et al 1983;Mishra et al 1997;Verma et al 2005;Chiu et al 1981;Chiu et al 1983;Raghavan et al 2009;Srivastava et al 1988;Verma et al 2005). These compounds have been shown to increase agonist binding to DA D 2 receptors without affecting antagonist binding, and prevent conversion of high-affinity state DA receptors (D 2 High ) to their low-affinity state (D 2 Low ) (Mishra et al 1990;Srivastava et al 1988;Verma et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium and zinc ions (Schetz et al, 1999), amiloride and its nitrogen-substituted derivatives (Hoare and Strange, 1996), and analogs of the tripeptide proline-leucine-glycine (PLG) (Verma et al, 2005) were suggested to interact allosterically with D 2 receptors. More recently, the distinctive in vivo profiles of (3S)-3-[3-(methylsulfonyl)phenyl]-1-propylpiperidine hydrochloride [(Ϫ)-OSU6162] and ACR16 (pridopidine) were suggested to involve allosteric actions at D 2 receptors, although supporting data are limited (Tamminga and Carlsson, 2002;Rung et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additional functional studies were conducted at the transcriptional level with SH-SY5Y human neuroblastoma cells, a cell line that has been extensively characterized with regards to CNS function (Hillion et al 2002;Nair et al 1996;Verma et al 2005). Real-time PCR using human-CRP40-specific primers revealed that this alternative splice variant of mortalin is differentially upregulated after exposure to the DA D 2 receptor antagonist, haloperidol, confirmed by absolute quantitation.…”
Section: Discussionmentioning
confidence: 99%